Expansão do crédito, comprometimento de renda e vulnerabilidade das famílias brasileiras na década de 2000 - Borges, Marco Antonio (2016)
This paper investigates the determinants of household debt-service ratio, using disaggregate data from the Household Budget Surveys of 2002/2003 and 2008/2009 from IBGE. The results show strong evidence of the influence of payroll loans on the increase of debt-service ratio in Brazilian families in the period considered. It was also found that indebtedness is associated with the occurrence of financial difficulties affecting spending on housing, health and food at the household. Assessing the influence of debt on the likelihood of financial difficulties, we conclude that the existence of debt increases more strongly the vulnerability of families whose heads are female, over the age of 60, with more than 11 years of schooling or belonging to the 40% higher incomes. In households headed by women, the impact of debt on financial vulnerability can be attributed to socioeconomic factors and adds to the already high vulnerability of these families. In the other cases identified (householders over 60 years, more than 11 years of schooling and families between the 40% higher income) financial vulnerability is lower, but the impact of debt is greater than average due to the high debt-service ratio. This may indicate an inadequate volume, interest rate or term in the credit offered to this segment.